Prevalence and Antimicrobial Susceptibility Pattern of Coagulase- Negative Staphylococci (CoNs) Causing Bacteremia in Sheikh Zayed Hospital - Aziz, Sadia; Ahmed, Bilal; Mansha, Iqra; Ali, Zarmeen Zahra; ZESHAN, MUHAMMAD; RAFEAQ, MUHAMMAD HAMZA; ZAHEER, WAQAR; JAHANZEB, ASIA (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Coagulase-negative staphylococci (CoNs) have emerged as significant pathogens in bloodstream infections, particularly in hospital settings. Their increasing antibiotic resistance poses a major clinical challenge. Objective: To assess the prevalence, antibiotic resistance patterns, and demographic distribution of CoNs isolates in blood culture samples, along with the association of multidrug resistance (MDR) with gender and hospital units. Study Design & Setting: This cross-sectional study was conducted in a tertiary care hospital, analyzing blood culture samples from 350 patients. Materials and Methods: Blood samples were cultured to identify CoNs isolates. Antibiotic susceptibility was determined using the disk diffusion method. Resistance patterns were categorized by antibiotic class, and MDR was defined as resistance to three or more antibiotic classes. Data were analyzed using the chi-square test, with p < 0.05 CoNsidered statistically significant. Results: CoNs was detected in 30.3% of blood culture samples. Resistance was highest for penicillin (80%), amoxicillin (75%), and ceftriaxone (65%), with significant associations for beta-lactams and aminoglycosides (p < 0.05). MDR was more prevalent in CoNs cases (54.7%) compared to non-CoNs cases (24.6%) (p < 0.001). ICU had the highest CoNs prevalence (37.7%), followed by general wards (23.6%). No significant gender-based differences in antibiotic resistance were observed. Conclusion: CoNs infections are common in hospitalized patients, particularly in ICUs, with high resistance to beta-lactams and aminoglycosides. The high prevalence of MDR necessitates stringent antibiotic stewardship and infection control measures.